Identification of Separate Fractions on Kacapiring Leaf Simplisia - Yoga, Ida Bagus Ketut Widnyana; Suarta, I Wayan; Wrasiati, Luh Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 6 No 2 (2019): Scientific Journal of Food Technology (September)DO - 10.24843/MITP.2019.v06.i02.p03, 2020)
Identification compound of simplisia extract by Thin Layer Chromatography (TLC), is one way to obtain active component in Kacapiring leaf ( Gardenia jasminoides Ellis).The purpose of this research were to get the best crude e.xtract by organic solvent (ethanol, methanol, and ethyl acetate), and composition of the mobile phase to identify of the separate fractions by TLC. The separate fractions was calculated of Rf value and was scanned maximum wavelenght by spectrophotometer. The treatment was repeated three times, data colected was analysed by descriptive statistic. The result showed that the highest percent of extractive value to ethyl acetate (17.32 %) and the lowest was in ethanol (11.41 %). The best of mobile phase in ethanol crude extract was in mobile phase II (petroleum ether : acetone and 2-propanol 90 :10: 0.45) with 7 spots clearly, while methanol and ethyl acetate crude extract in mobile phase I (petroleum ether : acetone and 2-propanol 85:15:0.45), with separate respectively 8 and 9 spots. The identity average of compound showed that crude extract consist of chlorophyll a, chlorophyll b, lutein, feofitin, beta carotene, and some of spots still unknown identity. Ethyl acetate and mobile phase I were the best of solvent and mobile phase to extract and identify of Kacapiring simplisia.